2.2 C—C Bond Formation by Alkyl C—H Activation - Baudoin,O. (Catalytic Transformations via C-H Activation 2, 2015)
In comparison to the wealth of methods recently developed for the catalytic functionalization of the C(sp2)—H bonds of arenes and hetarenes, relatively little work has focused on the functionalization of the unactivated C(sp3)—H bonds of alkyl fragments. This chapter highlights selected examples of the fast-growing literature on the catalytic functionalization of unactivated C(sp3)—H bonds through organometallic C—H activation, with an emphasis on the most synthetically useful methods. It covers heteroatom-directed C(sp3)—H activation with regard to cross coupling with alkenes, alkynes, and carbon monoxide, organoboron reagents, diaryliodonium salts, and organic halides. Also included is C(sp3)—H activation/intramolecular C—C coupling induced by oxidative addition and nondirected intermolecular C(sp3)—H arylation.
Keywords: C(sp3)—H bond activation; carbon—carbon coupling; transition metals; palladium catalysis; ruthenium catalysis; alkylation